2020
DOI: 10.1002/tal.1751
|View full text |Cite
|
Sign up to set email alerts
|

Simplified procedures for seismic design verification and evaluation of lead rubber bearing base‐isolated buildings based on free‐vibration response

Abstract: SummaryBase isolation has seen widespread application to buildings and infrastructures over the past four decades. However, there is a lack of methods for assessing the performance of a base‐isolated structure at the end of construction and during its service life. To this end, simplified methods are developed for verifying isolation design and evaluating seismic demands of rubber‐bearing‐supported base‐isolated buildings based on their free‐vibration response, which could be obtained using field (on‐site) tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Base isolation is appropriate, primarily under the following conditions [ 31–33 ] : Low‐ to medium‐rise structures situated over stiff strata. Strata that do not exhibit long‐period predominant excitations. Large displacement capacity at the isolation level. …”
Section: Developing the Model For Analysismentioning
confidence: 99%
“…Base isolation is appropriate, primarily under the following conditions [ 31–33 ] : Low‐ to medium‐rise structures situated over stiff strata. Strata that do not exhibit long‐period predominant excitations. Large displacement capacity at the isolation level. …”
Section: Developing the Model For Analysismentioning
confidence: 99%
“…SBTs are seldom performed on real structures [43][44][45] since they require an important equipment to be constructed for the application of forces, which is often difficult to place in situ, with high costs, and also because this kind of test should be carefully designed to avoid possible damage to structural or non-structural components. However, the excitation level provided to the structure is similar to that provided by low-and medium-intensity earthquakes, which can occur during the life of buildings in earthquake prone areas.…”
Section: Dynamic Tests During the Infill Damagementioning
confidence: 99%
“…Rubber isolation bearings not only ensure the stability of the superstructure, but also effectively release stress.Park et al studied the dynamic performance of lead-rubber bearings and lead-free rubber bearings under seismic isolation, and found that the seismic performance of lead-free rubber bearings is due to the absence of lead-free rubber bearings. They also analyzed the dynamic response characteristics of lead-free bearings under horizontal and vertical seismic excitations [3].Similarly, Jamalvandi et al conducted a comparative study on lead rubber bearings and non lead rubber bearings for storage tanks and found that lead rubber bearings have high isolation efficiency [4].Lu et al developed a simplified method for verifying the free vibration response of lead rubber bearings and linear natural rubber bearings in isolation design and seismic demand assessment, and obtained corresponding formulas [5]. Cao et al proposed a lead rubber isolation bearing for multi-stage composite bridges that meets specific performance under different levels of seismic hazards to ensure isolation efficiency and limit the ability of bearings to move too much under different seismic effects.…”
Section: Introductionmentioning
confidence: 99%